Dampak Sosmed Addiction Disorder Terhadap Kesehatan Remaja - Sevilla Ukhtil Huvaid; Yulianita Yulianita (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
SMAN 9 is one of the favorite schools that has grown rapidly in the city of Padang. Based on the situation analysis conducted, it is known that in this high school there has never been any outreach to students about the negative impact of social media on their health and learning achievement. The existence of this high school which is located in Cyber Pasar Baru and Andalas University campus is certainly a threat to the health aspect and student achievement, because with this strategic location students have additional high enough access to be able to use social media such as in internet cafes ( internet cafe) without having to spend a lot of money to buy packages and this of course provides an opportunity for students to become social media addicts. For that reason, in this service program the team made SMAN 9 Padang City as a partner. The methods of activities carried out include doing pre-tests, counseling, showing videos about social media addiction disorder, discussions, doing post-tests, sharing experiences, and competitions about materials. Based on the community service activities carried out, it was found that there was an increase in the knowledge and motivation of the participants after attending the counseling. In addition, it was found that there was still a lack of attention and support from the puskesmas, schools, and families in an effort to increase their knowledge about the impact of excessive use of social media.